Loss-of-Function ABCC8 Mutations in Pulmonary Arterial Hypertension - Michael S. Bohnen; Lijiang Ma; Na Zhu; Hongjian Qi; Conor McClenaghan; Claudia Gonzaga‐Jauregui; Frederick E. Dewey; John D. Overton; Jeffrey G. Reid; Alan R. Shuldiner; Aris Baras; Kevin J. Sampson; et al. (2018)
Background: In pulmonary arterial hypertension (PAH), pathological changes in pulmonary arterioles progressively raise pulmonary artery pressure and increase pulmonary vascular resistance, leading to right heart failure and high mortality rates. Recently, the first potassium channelopathy in PAH, because of mutations in KCNK3 , was identified as a genetic cause and pharmacological target. Methods: Exome sequencing was performed to identify novel genes in a cohort of 99 pediatric and 134 adult-onset group I PAH patients. Novel rare variants in the gene identified were independently identified in a cohort of 680 adult-onset patients. Variants were expressed in COS cells and function assessed by patch-clamp and rubidium flux analysis. Results: We identified a de novo novel heterozygous predicted deleterious missense variant c.G2873A (p.R958H) in ABCC8 in a child with idiopathic PAH. We then evaluated all individuals in the original and a second cohort for rare or novel variants in ABCC8 and identified 11 additional heterozygous predicted damaging ABCC8 variants. ABCC8 encodes SUR1 (sulfonylurea receptor 1)—a regulatory subunit of the ATP-sensitive potassium channel. We observed loss of ATP-sensitive potassium channel function for all ABCC8 variants evaluated and pharmacological rescue of all channel currents in vitro by the SUR1 activator, diazoxide. Conclusions: Novel and rare missense variants in ABCC8 are associated with PAH. Identified ABCC8 mutations decreased ATP-sensitive potassium channel function, which was pharmacologically recovered.